The Causal Factors of Building Construction Defects - Arman, Utami Dewi; Melasari, Jihan; Sari, Afrilda; Sari, Kharisma Permata (CIVED, 2024)
Defects are something that must be identified in the implementation of quality management. Defects can potentially lead to construction failures and injury. This study aims to identify and analyse the causal factors of building construction defects based on the perspective’s project stakeholders. This research is quantitative-descriptive research conducted through questionnaires distributed to the purposive respondents. Then, conduct statistical analysis and evaluate the causal factors of construction defect using Failure Mode and Effect Analysis (FMEA). Based on the results, the critical causal factors of building construction defects are lack of communication within the project environment with a value of 33.6; poor performance of the project management team with a value of 30.3; improper design and specification with a value of 27.88; lack of supervision in the site with the value of 24.60 and lack of competency of the construction labour with the value of 23.04. Project stakeholders are expected to pay more attention to critical causal factors as preventive measures to prevent structural failure and injury.